1996
DOI: 10.1016/0304-3959(96)02955-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethnicity on prescriptions for patient-controlled analgesia for post-operative pain

Abstract: We studied if ethnicity influences patient-controlled analgesia (PCA) for the treatment of post-operative pain. Using a retrospective record review, we examined data from all patients treated with PCA for post-operative pain from January to June 1993. We excluded patients who did not have surgery prior to the prescription of PCA or were not prescribed PCA in the immediate post-operative period. The sample consisted of 454 subjects. While there were no differences in the amount of narcotic self-administered, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(99 citation statements)
references
References 10 publications
1
94
2
Order By: Relevance
“…These ideas merit additional study. Our findings are in line with previous published studies that note a higher postoperative opioid consumption in men [20,21] and patients who used opioids preoperatively [21]. The reason for a higher opioid consumption in men is unclear and might be related to a difference in effectiveness [22] but is also ascribed to sex differences in fear of addiction, previous pain experience, and tolerance to postoperative pain and opioid side effects [20].…”
Section: Discussionsupporting
confidence: 92%
“…These ideas merit additional study. Our findings are in line with previous published studies that note a higher postoperative opioid consumption in men [20,21] and patients who used opioids preoperatively [21]. The reason for a higher opioid consumption in men is unclear and might be related to a difference in effectiveness [22] but is also ascribed to sex differences in fear of addiction, previous pain experience, and tolerance to postoperative pain and opioid side effects [20].…”
Section: Discussionsupporting
confidence: 92%
“…Comparable racial/ethnic inequalities in receipt of opioid analgesics for acute pain, but not nonopioid analgesics, have been observed for different presenting complaints, including musculoskeletal pain and back pain [42,43,55]. Examination of the literature concerning postoperative care shows, irrespective of study design, surgical procedure investigated, patient age, or whether or not patient-controlled analgesia was administered, whites received higher doses of opioid analgesics than African Americans, non-Hispanic whites, or Asian Americans [62,72,73] or were more likely to receive analgesic medications adequate to their pain level [64]. More distressing, Jimenez et al [47] reported differences in perioperative analgesic prescribing between Latino and white children who had a tonsillectomy/adenoidectomy.…”
Section: Acute Nonmalignant Painmentioning
confidence: 99%
“…5 Though these studies 6,9,23 suggest that there is under treatment of African American patients leading to inadequate pain control, our study indicates that African American children have intrinsically higher morphine requirements for comfort after surgery. African American children had higher postoperative pain scores in the PACU after receiving identical morphine doses to Caucasian children.…”
Section: Discussionmentioning
confidence: 75%
“…Specifically, considerable evidence exists that African American and Hispanic patients report lower tolerance for experimentally induced pain compared with Caucasian adults. [2][3][4] In addition, several studies have revealed evidence of disparities in the prescription of opioid analgesics among racial and ethnic groups in the management of postoperative, 5 cancer, 6 and emergency department [7][8][9] pain in patients across all ages, including children.…”
Section: Discussionmentioning
confidence: 99%